2021
DOI: 10.21203/rs.3.rs-680517/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oceanic Drivers and Empirical Prediction of Interannual Rainfall Variability in Late Summer Over Northeast China

Abstract: Northeast China (NEC) is located between the subtropical monsoon and temperate-frigid monsoon regions and exhibits two successive rainy seasons with different natures: the northeast cold vortex rainy season in early summer (May–June) and the monsoon rainy season in late summer (July–August). Summer rainfall over NEC (NECR) has a fundamental influence on society, yet its successful seasonal prediction remains a long-term scientific challenge to current dynamical models. The poor NECR prediction skill is partly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…This correlation pattern weakens in spring (Figure 3b) but becomes stronger in the tropical North Atlantic (TNA) in summer (Figure 3c). The positive (negative) SST anomalies over the TNA also persist from winter to summer, and these anomalies can enhance (suppress) the western North Pacific anomalous anticyclone (WNPAC) through zonal westward extension of the overturning circulation over the Pacific-Atlantic Ocean (Hong et al, 2014;Zhao et al, 2022Zhao et al, , 2023Zuo et al, 2019Zuo et al, , 2020, which can affect the HNSP A directly. Thus, the JA NAT A predictor reflects the remote and transseasonal impacts of the North Atlantic on HNSP A .…”
Section: Interannual Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation pattern weakens in spring (Figure 3b) but becomes stronger in the tropical North Atlantic (TNA) in summer (Figure 3c). The positive (negative) SST anomalies over the TNA also persist from winter to summer, and these anomalies can enhance (suppress) the western North Pacific anomalous anticyclone (WNPAC) through zonal westward extension of the overturning circulation over the Pacific-Atlantic Ocean (Hong et al, 2014;Zhao et al, 2022Zhao et al, , 2023Zuo et al, 2019Zuo et al, , 2020, which can affect the HNSP A directly. Thus, the JA NAT A predictor reflects the remote and transseasonal impacts of the North Atlantic on HNSP A .…”
Section: Interannual Prediction Modelmentioning
confidence: 99%
“…These results indicated that the SD prediction model outperformed the dynamic model predictions to some extent. Inspired by the timescale decomposition approach, Zhao et al (2022) established an oceanic driver and empirical prediction of interannual precipitation variability in late summer over Northeast China, drastically improving the region's prediction accuracy. Additionally, the hybrid statistical downscaling prediction model (HSDPM), which integrates well-known external forcing signals with effective dynamic model predictions, has recently emerged as a new method for short-term climate prediction.…”
Section: Introductionmentioning
confidence: 99%
“…However, state‐of‐the‐art dynamical models commonly exhibit essential biases in simulating the ENSO‐related characteristics largely owing to the common excessive Pacific cold tongue bias (G. Li et al., 2019), seriously limiting the prediction skill of the EASM (Huang et al., 2018; Y. Liu et al., 2019; B. Liu et al., 2021; Zhu et al., 2020). The statistical models have a relatively higher skill in predicting the EASM (B. Liu et al., 2021; Z. Wu et al., 2009; Yim et al., 2016; Zhao et al., 2022). But there still exists a deficient capture for the ENSO characteristics in the statistical models, such as the EDR.…”
Section: Introductionmentioning
confidence: 99%